2003
DOI: 10.1210/en.2002-220650
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of the Adenosine 5′-Triphosphate-Binding Cassette Transporter A1 in the Externalization of Annexin I from Pituitary Folliculo-Stellate Cells

Abstract: Annexin 1 (ANXA1) has a well-demonstrated role in early delayed inhibitory feedback of glucocorticoids in the pituitary. ANXA1 is located in folliculo-stellate (FS) cells, and glucocorticoids act on these cells to externalize and stimulate the synthesis of ANXA1. However, ANXA1 lacks a signal sequence so the mechanism by which ANXA1 is externalized from FS cells was unknown and has been investigated. The ATP-binding cassette (ABC) transporters are a large group of transporters with varied roles that include th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 54 publications
1
58
2
Order By: Relevance
“…The inhibition of ABCA1-mediated cholesterol efflux by BLT-4 prompted us to determine if the ABCA1 inhibitor glyburide (29,31,(46)(47)(48)(49)(50)(51) (Fig. 1A) As expected from previous studies (29,31,(48)(49)(50), glyburide inhibited ABCA1-mediated [ 3 H]cholesterol efflux from HEK[ABCA1] cells to apoA-I (10 g protein/ml) with an IC 50 of ‫003ف‬ M (Fig.…”
Section: Effects Of the Abca1 Inhibitor Glyburide On Sr-bi-mediated [mentioning
confidence: 58%
See 2 more Smart Citations
“…The inhibition of ABCA1-mediated cholesterol efflux by BLT-4 prompted us to determine if the ABCA1 inhibitor glyburide (29,31,(46)(47)(48)(49)(50)(51) (Fig. 1A) As expected from previous studies (29,31,(48)(49)(50), glyburide inhibited ABCA1-mediated [ 3 H]cholesterol efflux from HEK[ABCA1] cells to apoA-I (10 g protein/ml) with an IC 50 of ‫003ف‬ M (Fig.…”
Section: Effects Of the Abca1 Inhibitor Glyburide On Sr-bi-mediated [mentioning
confidence: 58%
“…However, their common abilities to mediate cholesterol efflux from cells led us to probe their activities using small molecules that had previously been shown to inhibit their lipid transport activities. These included small molecules that block lipid transport (BLTs) mediated by SR-BI (45) and the drug glyburide (29,31,(46)(47)(48)(49)(50)(51), which blocks ABCA1-mediated cholesterol efflux.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Further studies have shown that the initial steroid-induced exportation of the native protein is effected via a novel, GCreceptor mediated, non-genomic signalling mechanism involving PI3-kinase, MAP-kinase and PKC. 18 In addition, they have provided functional and histological evidence that the translocation of the protein across the plasma membrane is effected via a member of the ATP binding cassette family of proteins (ABC A1 20 ). In particular, confocal imaging has demonstrated co-localization of annexin 1 and the ABC A1 annexin 1 and neuroendocrine function 219 transport protein at junctions of follicostellate cells and corticotrophs, suggesting that annexin 1 may subserve a juxtacrine role.…”
Section: Mechanism Of Annexin 1 Actionmentioning
confidence: 99%
“…Glucocorticoids cause the export of Anx A1 which is evident after 30 mins and maximal at 90 mins. The ATP-binding cassette (ABC) transporter family is known to export a number of proteins, including bFGF [67] and Anx A1 in inflamed gut mucosa [69]. Glyburide, an ABC transporter inhibitor, markedly inhibits glucocorticoidstimulated (but not potassium-stimulated) export of Anx A1from TtT/GF cells and from pituitary tissue [69].…”
Section: Mechanisms Of Externalisation Of F-s Signalling Moleculesmentioning
confidence: 99%